Clinical diagnosis and treatment of immune checkpoint inhibitor‐associated adverse events in the digestive system. Issue 4 (28th February 2020) - Li, Yue; Kang, Xiaohui; Wang, Hanping; Guo, Xiaoxiao; Zhou, Jiaxin; Duan, Lian; Si, Xiaoyan; Zhang, Li; Liu, Xiaowei; Qian, Jiaming; Zhang, Li
Abstract : Immunotherapy for malignant tumors is a hot spot in current research and the treatment of cancer. The activation of programmed cell death receptor‐1 (PD‐1) and cytotoxic T lymphocyte‐associated antigen 4 (CTLA)‐4 relevant signaling pathway can inhibit the activation of T lymphocytes. Tumor cells can achieve immune escape by activating this signaling pathway. By inhibiting this signaling pathway, immune‐checkpoint inhibitors (ICIs) activate T lymphocytes to clear the tumor cells. Therefore, the adverse effects of ICIs are mainly immune‐related adverse events (irAEs). The digestive system, including the gastrointestinal tract and liver which are vital organs of digestion and absorption, metabolism and detoxification, as well as important immune‐related organs, is the most commonly affected system of irAEs. This review explains the incidence, clinical features, diagnosis and treatment of liver and gastrointestinal adverse events in ICIs.